Fatores inibidores da institucionalização do processo orçamentário em hospitais - Bacchi, Thalita Severo (2023)
The research aimed to analyze the inhibiting factors of the institutionalization of the budget, as a managerial practice in a philanthropic hospital. To achieve this goal, a case study was developed in a philanthropic hospital. For data analysis we used the categorical content analysis model, with regard to the analytical categories used, these were defined according to the model of Frezatti et al. (2011). The results indicate the validity of the proposed theoretical model. The application of the model in the Hospital allowed us to conclude that although the presence of inhibitory factors in the institutionalization of the budget process of the studied organization is visible, there seems to be little effort to solve them, indicating a preference for stability and determined resistance to change. This is because the Institution has a very strong and very rigid organizational culture, so, due to this resistant cultural structure, the board is the one who holds the final decision-making power, making the Institution more resistant to changes and limiting the collaboration of other managers. It was observed that several factors considered in the literature as inhibitors of the institutionalization process were identified and, if the organization chooses to effectively use the budget process to support management, the first step would be to end the centralization of decisions in senior management. In this way, the other sectors would have an easier time influencing decisions and presenting their visions, thus enabling the Institution to develop realistic and achievable strategies. However, the problems arising from the lack of planning and integration between the various areas of the Hospital were evident in the way managers mention the lack of knowledge of the use of the budget, so the integration between managers could be achieved with greater stimulus to interaction. However, the centralization of decision-making power in senior management ends up discouraging the exchange of experiences and information, in view of the observation of a scenario in which the method used in the management of the referred Hospital is predominantly top down. In this perspective, the findings highlight that the problems related to the budget process of the Hospital are associated with the way this process is executed, and not with the practice itself, supporting the main thesis of Frezatti et al. (2011). However, the results of this study contribute to the knowledge about the inhibiting factors of the institutionalization of the budget process and about how the relationship between these factors can create dysfunctional mechanisms that prevent the proper use of this management practice. Still, this research reinforces the view that it is necessary to understand more deeply the interaction between the elements that make up the budget process and that an important way is the research that analyzes them in an integrated way. Among the possible limitations of the research, it was identified the fact that this study covers only one health institution, for this reason, it is clear that the conclusions cannot be generalized to other hospital entities.